Audit team reporting of the time from an agency theory Perspective - Basheer Ghani Khudhair Atrah (Journal of Madenat Alelem University College, 2017)
Many studies investigated the importance of time budgets on the auditing operation which will be done by the auditor team. This will be affected on the selection of the clients as well as the managers incentives however there are a decreasing on the focusing of the time budgets fulfillment and this needs to investigate the reasons of why the real hours is more than the planning hours.